CIKAMPAK FASHION OUTLET MARKETING COMMUNICATION STRATEGY IN INCREASING PUBLIC INTENTION TO BUY - Vina Ovi Melinda; Syahrul Abidin (KABILAH : Journal of Social Community, 2022)
Abstract: The marketing communication strategy is designed to determine the goals and direction of marketing in a business related to positioning, objectives and elements of the marketing mix. This qualitative study aims to obtain information about the communication plan in the field of marketing carried out by the Cikampak Fashion Outlet to increase the willingness to buy in the community. This study involved shop owners and several store employees who were positioned as research informants. This research uses qualitative research with direct observation techniques and data collection through interviews. This research focuses on how the product quality strategy and pricing strategy at Fashion Outlet Cikampak increase people's buying interest. Reducing data, presenting facts, and drawing conclusions are the methods of data analysis in this study. The results obtained indicate that Fashion Outlet Cikampak has a successful marketing communication plan that increases consumer interest in the advertised goods. This shows that, to achieve the desired target market, companies must develop a well-thought-out marketing strategy to achieve the initial goals. Keywords: Marketing Communication Strategy, Public Purchase Intention